Crime of baby dumping: a review of Islamic, Malaysian and Nigerian laws - Mohd, Azizah; Alkali, Alhaji Umar (UPM Press, 2015)
Islam prohibits all acts that endanger the life of a child or exposes children to abuse including dumping of babies. Those acts are crimes punishable under the law. In a similar vein, internationally, baby dumping and all acts that expose children to danger are prohibited under the United Nation’s Convention on the Rights of the Child 1989 (CRC). Malaysia and Nigeria, like most nations of the world, are signatories to most international legal frameworks on child protection including the CRC. In Malaysia and Nigeria, baby dumping is an alarming phenomenon. Many babies suffer or even die as a result of the act of baby dumping. This article intends to examine the laws relating to the protection of babies from dumping in Malaysia and Nigeria. Discussions will include the position of baby dumping in Islam to serve as a comparison. Examination will extend to analysis on whether the laws in Malaysia and Nigeria are adequate to address the problem of baby dumping and to fully protect children from baby dumping. The study is basically a library based research where reference is made to books and articles. A comparative legal research methodology is employed in looking at the positions in Islam, Malaysia and Nigeria. It is hoped that the findings on child protection laws, particularly those related to baby dumping in the Islamic, Malaysian and Nigerian laws, will provide better protection for babies and prevent them from being dumped.